PREDIKSI EROSI DENGAN METODE USLE DI PERKEBUNAN KELAPA SAWIT PTPN XIII GUNUNG MELIAU KECAMATAN MELIAU KABUPATEN SANGGAU - Putri Liastuti; Tino Orciny Chandra; Bambang Widiarso (Fakultas Pertanian Universitas Tanjungpura, 2021)
The research location that is in Afdeling 3 PTPN XIII Mount Meliau Meliau District of Sanggau. This study aims to predict the magnitude of the erosion and the amount of erosion that can still be tolerated. The method used in this study was calculated using the USLE by knowing the value of the R factor, K, L, S, C and P which are the root causes of erosion in the area of oil palm plantations in the study sites. Further erosion of values that can be tolerated in comparison to the predicted value erosion. Having compared the predictive value of the erosion of the value erosion that can be tolerated, it is necessary to do the conservation measures recommended.The results of this study found that the rate of erosion prediction (A) reached 140.16 to 9737.28 tons / ha / year. Value erosion prediction that can be tolerated (Etol) ranged from 48.22 to 32.13 tonnes / ha / year. In Ult4 land value (A) is greater than the value of Etol with moderate erosion hazard level, while on land Ult18, Ult24, Ult36 value (A) is greater than the value of Etol with severe erosion hazard level. Planning and prevention of erosion is the appropriate planting bench terracing of good construction. Special to land Ult4 and Ult18 can in recommend also with planting LCC and making the porch kontruksi was.